Atmospheric Chloride Leaching: The Way Forward For Nickel Laterites - Bryn Harris (The Minerals, Metals and Materials Society, 2003)
Chesbar Resources Inc.1 is developing a nickel-cobalt laterite project in Guatemala, Central America, by applying existing atmospheric chloride technology to a known resource. The tropical laterite project has an inferred resource of 133 million tonnes grading 1.51% nickel, which represents ~20% of Chesbar?s land holdings in Guatemala. Within its boundaries, the Sechol area has a measured resource of 14 million tonnes grading 1.46 % nickel and 0.08% cobalt, and an indicated resource of 23 million tonnes grading 1.34% nickel and 0.08% cobalt. Notwithstanding the impressive overall resource, the company has taken an innovative approach to a laterite project and is concentrating on El Inicio, a high-grade starter pit with five million tonnes grading 2.1% nickel and 0.08 % cobalt. The process flowsheet is based on atmospheric chloride leaching in a slightly acidic magnesium chloride brine, solution purification by recycled magnesia, precipitation of a mixed nickel/cobalt hydroxide intermediate product, and lixiviant regeneration by modified pyrohydrolysis technology. Initial results suggest that >90% of the contained nickel and cobalt in the non-magnetic fraction of the feed can be recovered, with <5% of the iron leaching. A metallurgical scoping study has established preliminary capital and operating costs for a production facility at a proposed rate of 20,000 tonnes per year of nickel as the intermediate mixed hydroxide. A preliminary assessment of producing a magnesium oxide by-product has also been carried out. This paper reports on the current development of the project and highlights the advantages of working in a chloride medium at atmospheric pressure and slightly elevated temperatures.